The deubiquitinase USP8 regulates ovarian cancer cell response to cisplatin by suppressing apoptosis - Corno, Cristina; D’Arcy, Padraig; Bagnoli, Marina; Paolini, Biagio; Costantino, Matteo; Carenini, Nives; Corna, Elisabetta; Alberti, Paola; Mezzanzanica, Delia; Colombo, Diego; Linder, Stig; Arrighetti, Noemi; et al. (Frontiers in Cell and Developmental Biology, 2022)
The identification of therapeutic approaches to improve response to platinum-based therapies is an urgent need for ovarian carcinoma. Deubiquitinases are a large family of ubiquitin proteases implicated in a variety of cellular functions and may contribute to tumor aggressive features through regulation of processes such as proliferation and cell death. Among the subfamily of ubiquitin- specific peptidases, USP8 appears to be involved in modulation of cancer cell survival by still poorly understood mechanisms. Thus, we used ovarian carcinoma cells of different histotypes, including cisplatin-resistant variants with increased survival features to evaluate the efficacy of molecular targeting of USP8 as a strategy to overcome drug resistance/modulate cisplatin response. We performed biochemical analysis of USP8 activity in pairs of cisplatin-sensitive and -resistant cells and found increased USP8 activity in resistant cells. Silencing of USP8 resulted in decreased activation or receptor tyrosine kinases and increased sensitivity to cisplatin in IGROV-1/Pt1 resistant cells as shown by colony forming assay. Increased cisplatin sensitivity was associated with enhanced cisplatin-induced caspase 3/7 activation and apoptosis, a phenotype also observed in cisplatin sensitive cells. Increased apoptosis was linked to FLIPL decrease and cisplatin induction of caspase 3 in IGROV-1/Pt1 cells, cisplatin-induced claspin and survivin down-regulation in IGROV-1 cells, thereby showing a decrease of anti-apoptotic proteins. Immunohistochemical staining on 65 clinical specimens from advanced stage ovarian carcinoma indicated that 40% of tumors were USP8 positive suggesting that USP8 is an independent prognostic factor for adverse outcome when considering progression free survival as a clinical end-point. Taken together, our results support that USP8 may be of diagnostic value and may provide a therapeutic target to improve the efficacy of platinum-based therapy in ovarian carcinoma.